Peningkatan keterlibatan Siswa dalam Kegiatan Belajar Melalui Pemanfaatan Media Papan Keaktifan dari Sampah Gelas Plastik - Siti Maisaroh; Noer, Addely Damayanti; Pritasari, Ade Cyntia; Puspitasari, Aditya Dyah; Jannah, Ana Naimatul (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
The use of plastic cups is one of the teacher's efforts as a board medium for assessing student activity. The media used in class is very important to support successful learning in class. Media is material, or events that build conditions that enable students to acquire knowledge, skills or attitudes. The use of this glass is expected to be able to improve the quality of students at SDN Dasok 3. This research aims to determine the steps for using plastic cups as a board medium to assess the activity of grade students at SDN Dasok 3. The use of plastic cups as a board medium to assess the activity of class students. SDN Dasok 3. This research uses descriptive qualitative methods. Based on the research results, the steps for using plastic cups as a board medium to assess the activity of students at SDN Dasok 3 are cutting cardboard, cutting plastic cups, writing students' names, cutting grades, making hangers. Utilization of Plastic Cups as Board Media to Assess the Activeness of Students at SDN Dasok 3, namely students are more active in class, students are more enthusiastic in learning, students are bolder in conveying their ideas, student creativity is increasing.